2017
DOI: 10.1017/s1041610217001983
|View full text |Cite
|
Sign up to set email alerts
|

Discussing advance care planning: insights from older people living in nursing homes and from family members

Abstract: ACP was a welcome intervention for the majority of participants, but an individualized assessment of the person's readiness to be involved in ACP is needed. For people with dementia, it is essential to identify the right time to introduce ACP before NH admission. Participants in our study suggested that ACP should include palliative care and practical issues, and that in the NH setting all staff and family members may have a valuable role in ACP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 30 publications
4
50
0
Order By: Relevance
“…43,45,4855,5760,6264,66,6972,7477,7981,83 Abilities included difficulties reading and understanding documentation 58,60 and remembering ACP decisions. 59,60,66,70 The focus was on early engagement, prior to potential physical or cognitive deterioration 43,45,48,5155,5760,62,64,66,71,72,74,75,77,7981 where ‘… the person may already be too sick to interpret their treatment preferences’. 43 Early engagement meant ‘… meaningful plans could be put in place […] so that the patient’s quality of life could be enhanced …’ 80 and that decisions could be reassessed throughout the frail elders’ end-of-life trajectory.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43,45,4855,5760,6264,66,6972,7477,7981,83 Abilities included difficulties reading and understanding documentation 58,60 and remembering ACP decisions. 59,60,66,70 The focus was on early engagement, prior to potential physical or cognitive deterioration 43,45,48,5155,5760,62,64,66,71,72,74,75,77,7981 where ‘… the person may already be too sick to interpret their treatment preferences’. 43 Early engagement meant ‘… meaningful plans could be put in place […] so that the patient’s quality of life could be enhanced …’ 80 and that decisions could be reassessed throughout the frail elders’ end-of-life trajectory.…”
Section: Resultsmentioning
confidence: 99%
“…43 Early engagement meant ‘… meaningful plans could be put in place […] so that the patient’s quality of life could be enhanced …’ 80 and that decisions could be reassessed throughout the frail elders’ end-of-life trajectory. 45,48,52,5759,6264,69,76,81,83 For professionals, personal ability related to the knowledge and skills they required to proactively use and create ACP opportunities. Recommendations ranged from needing a greater understanding of what ACP meant, 72 to the ability to address cultural, socio-demographic and educational influences, 76 answer existential questions, 65 help frail elders connect ACP with their own values and beliefs, 56 and cross-sectoral liaison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they concluded that the capacity of some people with intellectual disabilities in terms of being able to understand would be a barrier to disclosure. Similarly, people with dementia have expressed how their views and opinions need to be listened to regarding their choice of care at the end of life even though their dementia affects their confidence in terms of such expression (Ingravallo et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly persons with early-stage Alzheimer’s disease did not reflect on future care,40 and elderly persons with dementia were not always able or wanted to discuss future care 41. Finally, most nursing home patients in a study of experiences with ACP expressed a desire not to think about the future and instead preferred to “live for the day” 42. Future not being important to patients in this study may partly be a consequence of their cognitive impairment;40,43 however it could relate to patients trusting health care professionals in making the right decisions for them, a finding also found by others 44.…”
Section: Discussionmentioning
confidence: 99%